Strategies for Increasing the Role of Family Medicine in Mexican Health Care Reform - Ramírez Aranda, José Manuel; Van Weel, Chris; Goodyear Smith, Felicity (American Board of Family Medicine, 2017)
There is little or no role for primary care and family medicine in current health reforms in Mexico. However, robust evidence shows that primary care helps prevent morbidity and mortality and increases health equity. Mexico has participated in several international meetings sponsored by the World Organization of National Colleges, Academies and Academic Associations and the North American Primary Care Research Group that are aimed at increased understanding of national health systems and the need to strengthen primary care for improved health outcomes. From 1 of these meetings the Cancu´n Manifesto emerged, with a strategic plan to increase the stature and impact of the Mexican College of Family Physicians (COLMEXAC) in strengthening primary care in Mexico. We aim to describe this strategic plan and discuss its early implementation, and for this account to serve as a possible formula for other countries. The 5 speciﬁc strategies discussed are 1) the need for consensus on the leading role of the Mexican family physician in the national health system; 2) health ecology research; 3) to improve the perception of patients about the beneﬁts of primary care and family medicine; 4) to organize meetings of health providers, users, and other stakeholders; and 5) to promote the professionalization of COLMEXAC as a legal entity. (J Am Board Fam Med 2017;30:843–847.) Keywords: Access to Health Care, Delivery of Health Care, Health Care Reform, Health Policy, Mexico, Universal Coverage